The scope of freedom of expression and the notion of ‘expressive conduct’ in the practice of the Hungarian Constitutional Court - Koltay András (HUNGARIAN JOURNAL OF LEGAL STUDIES, 2025)
Since 2018, the Constitutional Court of Hungary has decided several cases relating to symbolic speech and opinions expressed through actions (‘expressive conduct’). This paper attempts to review and critique these judgments in light of the relevant ECtHR jurisprudence. The scope of freedom of expression and the protection of speech are related but fundamentally different issues. Certain acts, even without constituting actual speech, are clearly protected by freedom of expression. The lines can be difficult to draw, and speech (expressive conduct) that is outside the scope is not covered by the constitutional protection of freedom of expression. However, where the speech or action is within the scope, the compatibility of the speech restriction applied with the protection of freedom of expression must still be examined. The paper argues that in some cases the conduct in question was unjustifiably excluded from the scope of freedom of expression by the Constitutional Court. Moreover, in the cases examined, the Court did not apply the appropriate fundamental rights tests, not even in cases where the exercise of freedom of expression was recognised.